Public research spin-offs in Germany: Summary report - Jürgen Egeln; Sandra Gottschalk; Christian Rammer; Alfred Spielkamp (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
The growing importance of knowledge and the ensuing need to translate research results, and especially new scientific findings as quickly as possible into economic activities are drawing the attention of academia and politicans increasingly towards what is referred to as academic spin-off formations. These business foundations from higher education institutions and off-campus research facilities are a route to knowledge and technology transfer, which can ensure that the research results gathered in these facilities are transferred directly into marketable products or processes. Policymakers are expected to create favourable framework conditions for the formation of spin-offs. Several initiatives of the Federal State and Länder (e.g. the EXIST Programme of the BMBF) were started with the express goal of promoting and aiding such new businesses.
urn:nbn:de:bsz:180-madoc-9685
Keywords: 330; Forschungskooperation; Betriebsaufspaltung; Unternehmensgründung; Öffentliche Forschung; Unternehmensentwicklung; Deutschland